Budget Participation and Budget Goal Commitment: Does Religiosity Play a Role? - Jusoh, Ruzita; L.S Sabbah, Yousef; Zainuddin, Suria (Asian Journal of Accounting Perspectives, 2022)
Research aim: This paper investigates whether religiosity, within a goal-setting context, affects goal commitment as well as moderates budget participation and budget goal commitment relationship. Design/Methodology/ Approach: A questionnaire survey was used to collect data from managers at public listed companies in Jordan. A total of 178 samples was used for data analysis. Research finding: Based on partial least squares (PLS) analysis, as expected, this study found that the relationship between budget participation and budget goal commitment is positive and strongly significant. Religiosity shows a significant and positive relationship with budget goal commitment. However, contrary to expectation, religiosity does not moderate the relationship between budget participation and budget goal commitment. Practitioner/ Policy implication: This paper is beneficial in understanding how religiosity governs an individual’s workplace behavior, particularly in the budgeting context. Research limitation: Due to the cross-sectional survey, this study has several limitations. One limitation is, the results may be influenced by common limitations associated with the survey research method, such as dishonest answers, hidden agendas of the respondents, and unanswered questions. Keywords: Budget Participation, Budget Goal Commitment, Religiosity, Jordan Type of article: Research paper JEL Classification: M41